Enhancing Government Communication through Digital Media: A Study of Community Perceptions in Oihu Village, Wakatobi - Wa Ode Anita Ahmad; Harry Fajar Maulana; Ansar Suherman (Jogjakarta Communication Conference (JCC), 2026)
This study investigates the use of digital media in government communication in Oihu Village, Wakatobi, and examines the community's perceptions of its effectiveness. The shift from traditional to digital communication methods, including WhatsApp, Facebook, and the village website, was evaluated based on interviews and field observations with government officials and residents. The research utilized qualitative methods, specifically content analysis, to explore key themes such as communication patterns, benefits, challenges, and strategies for further development. The findings reveal that digital media has enhanced accessibility, transparency, and public participation, although challenges related to infrastructure and digital literacy remain. Active digital users reported a positive impact on communication efficiency, while less digitally literate residents expressed concerns about exclusion from the benefits of digital tools. The study highlights the need for targeted efforts to bridge the digital divide, including improving infrastructure and promoting digital literacy. These findings contribute to the literature on digital governance and provide practical recommendations for enhancing government communication in rural areas.